2014
DOI: 10.1093/czoolo/60.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Foraging site recursion by forest elephants Elephas maximus borneensis

Abstract: Recursion by herbivores is the repeated use of the same site or plants. Recursion by wild animals is rarely investigated but may be ubiquitous. Optimal foraging theory predicts site recursion as a function of the quality of the site, extent of its last use, and time since its last use because these influence site resource status and recovery. We used GPS collars, behaviour and site sampling to investigate recursion to foraging sites for two elephant Elephas maximus borneensis herds in the Lower Kinabatangan Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 67 publications
4
26
0
Order By: Relevance
“…The approach in this paper provides a step forward in the ongoing attempt to incorporate cognition and memory in movement analyses (Avgar et al, 2015;Börger, Dalziel, & Fryxell, 2008;Fagan et al, 2013;Oliveira-Santos, Forester, Piovezan, Tomas, & Fernandez, 2016). Our method goes beyond previous approaches that investigate traplining (Ohashi, Leslie, & Thomson, 2008) or periodicity in recursive movement patterns (Bar-David et al, 2009;English et al, 2014;Giotto, Gerard, Ziv, Bouskila, & Bar-David, 2015). In our models, time since last visit to locations is a spatially explicit feature that influences movement decisions in combination with information on territory geometry and prey densities.…”
Section: Discussionmentioning
confidence: 99%
“…The approach in this paper provides a step forward in the ongoing attempt to incorporate cognition and memory in movement analyses (Avgar et al, 2015;Börger, Dalziel, & Fryxell, 2008;Fagan et al, 2013;Oliveira-Santos, Forester, Piovezan, Tomas, & Fernandez, 2016). Our method goes beyond previous approaches that investigate traplining (Ohashi, Leslie, & Thomson, 2008) or periodicity in recursive movement patterns (Bar-David et al, 2009;English et al, 2014;Giotto, Gerard, Ziv, Bouskila, & Bar-David, 2015). In our models, time since last visit to locations is a spatially explicit feature that influences movement decisions in combination with information on territory geometry and prey densities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gorilla's Gorilla gorilla beringei return interval to foraging patches was related to food abundance and quality (Watts 1998). Forest elephants Elephas maximus borneensis spending more time at a foraging site were likely to revisit it at longer intervals (English et al 2014). Frankfurt, Frankfurt (Main), Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Based on GPS data, behavioral sampling and measuring abiotic and biotic site characteristics, they found that recursive site-use was a function of the intensity of the last use, as expected by optimal foraging theory (Charnov et al, 1976). Additionally, English et al (2014) found two peaks in recursion behavior, one recursion occurring within two days of the initial visit, with another occurring between five and eight months since the previous visit. Immediate recursions were typically brief, while recursions occurring after a long absence were longer.…”
Section: Contributions To the Special Columnmentioning
confidence: 76%
“…Berger-Tal and Saltz (2014) discuss how GPS technology serves as an aid to managers post reintroduction of animals, and provide data from fallow deer and from oryx to support their argument. An additional four papers are original research papers that explore the relationship between animal behavior and its implications for conservation in fish (Paciorek et al, 2014), birds (Blesdoe and Blumstein, 2014;Kleindorfer et al, 2014) and, on a larger scale, elephants (English et al, 2014). Caro and Riggio (2014) review six species (and associated subspecies) of African 'trophy' mammals: ele-phants, black and white rhinoceros, lions, leopards, and buffalo.…”
Section: Contributions To the Special Columnmentioning
confidence: 99%
See 1 more Smart Citation